Alternatives to refugee camps: Cities need international support for receiving forcibly displaced people - Nadine Biehler; David Kipp (Stiftung Wissenschaft und Politik (SWP), 2019)
More and more people are forcibly displaced for longer and longer. An increasingly large number of them find refuge in cities instead of camps. Although this offers opportunities for local integration, it places a heavy burden on city administrations and rarely corresponds to the wishes of host governments, who usually prefer forcibly displaced people to stay in camps outside cities. Even humanitarian organisations, such as the United Nations High Commissioner for Refugees (UNHCR), are often overwhelmed by urban refugee situations. In view of this, at the first Global Refugee Forum in Geneva on 17-18 December 2019, the German government should work to ensure that good practices for supporting affected cities are adapted and that new approaches are created.
Keywords: 320